2014
DOI: 10.1001/jamainternmed.2014.3634
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Bisphosphonate Use on Risk of Postmenopausal Breast Cancer

Abstract: IMPORTANCE Studies have shown that bisphosphonates may have antitumor and antimetastatic properties. Recently, observational studies have suggested a possible protective effect of bisphosphonates on breast cancer, but the effect of bisphosphonate use on risk of breast cancer has not been tested in randomized trials.OBJECTIVE To assess the relationship of postmenopausal breast cancer incidence and bisphosphonate use using data from 2 randomized (1:1), double-blind, placebo-controlled trials. DESIGN, SETTING, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 52 publications
0
24
0
1
Order By: Relevance
“…In order to further address the possibility of confounding, Hue et al [28] examined the results of two randomized clinical trials designed to assess the efficacy of BP for the prevention of osteoporotic fractures (the Fracture Intervention Trial FIT [29] and the Once-Yearly Zoledronic Acid for Treatment of Postmenopausal Osteoporosis HORIZON pivotal trial [30]. Data were collected at clinical centers in the United States (FIT and HORIZON-PFT), in Asia and the Pacific, Europe, North America and South America (HORIZON-PFT).…”
Section: Discussionmentioning
confidence: 99%
“…In order to further address the possibility of confounding, Hue et al [28] examined the results of two randomized clinical trials designed to assess the efficacy of BP for the prevention of osteoporotic fractures (the Fracture Intervention Trial FIT [29] and the Once-Yearly Zoledronic Acid for Treatment of Postmenopausal Osteoporosis HORIZON pivotal trial [30]. Data were collected at clinical centers in the United States (FIT and HORIZON-PFT), in Asia and the Pacific, Europe, North America and South America (HORIZON-PFT).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, denosumab might have a tremendous clinical impact. In addition, there is ongoing research on the potential anti-cancer mechanisms of bisphosphonates as some ( 160 ) but not all ( 161 ) clinical trials on breast cancer have reported evidence for anti-tumor effects. This anti-neoplastic effects are plausible, considering that bisphosphonates may alter cellular signaling and responsiveness by modification in the isopentenyl diphosphate metabolism, untimely leading to cell death ( 162 , 163 ).…”
Section: Genomic Medicine In Osteoporosis Practicementioning
confidence: 99%
“…Prostate cancer cells also displayed a synergistic effect when treated with alendronate and simvastatin, thus inhibiting the mevalonate pathway at two different steps and significantly affecting survival and apoptotic pathways ( Rogers et al, 2015 ). Despite these anti-cancer properties, BP use does not reduce the risk of developing breast cancer in post-menopausal women, suggesting their anti-cancer properties still do not reduce initial development of non-skeletal cancer ( Hue et al, 2014 ). The known clinical applications and anti-neoplastic properties of BP are reviewed in Van Acker et al (2016) , while many clinical trials for the use of BP in cancer patients are still ongoing.…”
Section: Introductionmentioning
confidence: 99%